Permitting Morphologic Consort: Surah Youssef as an Example - Al – Maadhidi, Nabeelah (Journal of Tikrit university for humanities - مجلة جامعة تكريت للعلوم الانسانية, 2019)
Quran has a great importance in explaining speech meaning. These meanings may be individual collective and thus need explanation  and interpretation.  As such we need to determine these meaning by means of consorts that have clear eeffect upon  the direct the meaning. From morphological and grammatical perspectives, consorts includes language , it studies the structure of speech.  This will be the center of our research   .                                                                                                Permitting in morphologic consort surah Youssef as sample .We will speak about permitting in morphological structure and it ' s indication. Morphological forms express function meanings .Through these consorts it can be reached to insure guising that originates from vocabularies structure.It often comes(Subject)means(object)and unlike,and(feel)means(Subject)or(object)beside coming(faool) means (faeel) or(mafaool)…from appearances of permitting that we study in the research permitting in accordance including:type,number and gender,it is familiar that accordance represents type of concord ,the pot boil between parts of speech to form coordinated.unit,every   desecration to this arrangement can besaid permeation.